The prevalence of abdominal obesity and hypertension amongst adults in Ogbomoso, Nigeria - Amole, Isaac O. (Afr J Prim Health Care Fam Med, 2011)
BACKGROUND: In many developing countries obesity and obesity-related morbidity are now becoming a problem of increasing importance. Obesity is associated with a number of disease conditions, including hypertension, type 2 diabetes mellitus, cardiovascular diseases, cancer, gallstones, respiratory system problems and sleep apnoea. OBJECTIVES: The aim of this study was to determine the prevalence of hypertension and obesity, as classified according to waist circumference (WC), and further to determine whether there was any association between abdominal obesity and hypertension amongst adults attending the Baptist Medical Centre, Ogbomoso, Nigeria. METHOD: A cross-sectional descriptive study of 400 adults aged 18 years or older was conducted. Blood pressure and WC measurements were taken and participants completed a standardised questionnaire. RESULTS: A group of 400 participants were randomly selected (221 women; 179 men), with a mean age of 48.7 ± 16.6 years. The overall prevalence of obesity as indicated by WC was 33.8% (men = 8.9%; women = 53.8%). Women were significantly more sedentary than men (50.8% for men vs 62.4% for women, p < 0.05). Most of the obese participants’ families also preferred high-energy foods (85.2%, p > 0.05). Overall prevalence of hypertension amongst the study population was 50.5%, but without a significant difference between men and women (52.0% for men vs 49.3% for women, p > 0.05). The prevalence of hypertension amongst the obese subset, however, was 60.0%. CONCLUSION: Prevalence of abdominal obesity was found to be particularly significant amongst women in this setting and was associated with hypertension, physical inactivity and the consumption of high-energy diets.